2014
DOI: 10.3402/ejpt.v5.23911
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic pituitary thyroid axis and exposure to interpersonal violence in childhood among women with borderline personality disorder

Abstract: BackgroundA relationship between exposure to sexual violence and thyroid hormone alterations has been observed among women with posttraumatic stress disorder (PTSD). Women with borderline personality disorder (BPD) report a high estimate of childhood trauma.ObjectiveThe aim of the present study was to assess relationships between thyroid hormone measures and exposure to violence in childhood in women with BPD.MethodA total of 92 clinically euthyroid women with BPD (53% with comorbid PTSD) diagnosis and at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
2
24
0
2
Order By: Relevance
“…However, some studies have found the reverse biomedical symptomatology. Haviland et al (2006) report lower levels of T3 among sexually abused adolescent girls, and Sinai et al (2014) observed a lower fT3/fT4 ratio in women with borderline personality disorder (BPD) exposed to interpersonal violence during childhood. The reasons for these observed differences may include comorbid depression, the sex of the individual, as well as type, timing and duration of trauma exposure.…”
Section: Gestational States and Conditions That May Alter Or Intermentioning
confidence: 99%
“…However, some studies have found the reverse biomedical symptomatology. Haviland et al (2006) report lower levels of T3 among sexually abused adolescent girls, and Sinai et al (2014) observed a lower fT3/fT4 ratio in women with borderline personality disorder (BPD) exposed to interpersonal violence during childhood. The reasons for these observed differences may include comorbid depression, the sex of the individual, as well as type, timing and duration of trauma exposure.…”
Section: Gestational States and Conditions That May Alter Or Intermentioning
confidence: 99%
“…Except for concomitant borderline personality disorder (348), the common high-T3 syndrome in PTSD is at least partly due to increased step-up deiodination (179, 181, 182). Two studies in combat veterans of World War II and the Vietnam war revealed levels of total T4 and both total and free T3 to significantly correlate to severity of PTSD (181, 349).…”
Section: Thyroid Allostasis In Various Physiological and Pathologicalmentioning
confidence: 99%
“…Based on the consideration that the onset and course of hypothyroidism is often insidious and may be precipitated by maternal states and conditions that precede pregnancy, we were particularly interested in considering the role of stress exposure from a maternal life course perspective. We selected exposure to childhood maltreatment (CM) as our primary variable of interest for the following reasons: a) CM represents among the most pervasive and pernicious stressors affecting around one third of the general population, with life-long biological, psychological and behavioral consequences (e.g., Heim et al, 2010); b) we and others have previously demonstrated that a woman’s exposure to CM can produce alterations in several features of gestational biology that relate to embryonic/fetal development (Cammack et al, 2011; Mason et al, 2016; Moog et al, 2016; Shea et al, 2007); c) CM exposure has been associated with reduced thyroid activity in the non-pregnant state (Haviland et al, 2006; Machado et al, 2015; Sinai et al, 2014), with thyroid dysfunction in the postpartum period (Plaza et al, 2010; Plaza et al, 2012), and, more generally, with a higher risk of autoimmune disorders (Dube et al, 2009; Goodwin and Stein, 2004); and d) children of women exposed to CM exhibit an increased risk of developing some of the same behavioral disorders that have been observed in children with moderate maternal thyroid dysfunction (Miranda et al, 2013; Rijlaarsdam et al, 2014; Thompson, 2007). In light of these observations, we hypothesized that women exposed to CM may exhibit an increased likelihood of thyroid dysfunction in pregnancy, a time period of particular importance for not only the mother but also for her developing fetus.…”
Section: Introductionmentioning
confidence: 99%